Structure of source of finance of a company as a factor of external communication with a bank - Eljvira Gordon, Elja; Stanković, Aleksandra (Hotel and Tourism Management, 2013)
Communication in the framework of business and management expressed in terms of information data and instructions transfer is a function of particular importance both for internal and external stakeholders. The purpose of this study is to highlight the importance of the structure of company finance when communicating with a bank given that the highest level of skill of financial managers is to make an optimal combination of relations between the own and debt capital in the company. In this sense, as one of the factors of external communication between a company and a bank, the structure of sources of company’s finance is given a special attention. The contribution of this paper is therefore expressed through demonstration of external communication between a company and bank, through dissemination of information and business and financial decision making based on them.